Malaria vaccine approaches leveraging technologies optimized in the COVID-19 era - Kanoi, Bernard N.; Maina, Michael; Likhovole, Clement; Kobia, Francis M.; Gitaka, Jesse (Frontiers in Tropical Diseases, 2022)
Africa bears the greatest burden of malaria with more than 200 million clinical cases and more than 600,000 deaths in 2020 alone. While malaria-associated deaths dropped steadily until 2015, the decline started to falter after 2016, highlighting the need for novel potent tools in the fight against malaria. Currently available tools, such as antimalarial drugs and insecticides are threatened by development of resistance by the parasite and the mosquito. The WHO has recently approved RTS,S as the first malaria vaccine for public health use. However, because the RTS,S vaccine has an efficacy of only 36% in young children, there is need for more efficacious vaccines. Indeed, based on the global goal of licensing a malaria vaccine with at least 75% efficacy by 2030, RTS,S is unlikely to be sufficient alone. However, recent years have seen tremendous progress in vaccine development. Although the COVID-19 pandemic impacted malaria control, the rapid progress in research towards the development of COVID-19 vaccines indicate that harnessing funds and technological advances can remarkably expedite vaccine development. In this review, we highlight and discuss current and prospective trends in global efforts to discover and develop malaria vaccines through leveraging mRNA vaccine platforms and other systems optimized during COVID-19 vaccine studies.